Intraoral Scanners: Mechanism, Applications, Advantages, and Limitations - Kanika Singh Dhull; Rohit Nagar; Pranshu Mathur; Malabika Shil; Shrinidhi Jain; Roli Dureha; Abhay Kapoor (Wolters Kluwer Medknow Publications, 2024)
In recent years, the field of dentistry has witnessed remarkable technological advancements, one of which is the development and widespread implementation of intraoral scanners. These devices have revolutionized the way dental professionals capture accurate impressions of patients' oral cavities, offering several advantages over traditional impression-taking methods. To shed light on the impact of intraoral scanners on dentistry practice, this article explores their mechanism, uses, benefits, and limitations.